Prostate-Specific antigen: An overview and its current status in the diagnosis of prostate cancer - Siddalingeshwar Neeli (Indian Journal of Health Sciences and Biomedical Research KLEU, 2021)
Prostate-Specific Antigen (PSA), which has high organ specificity and poor cancer specificity, has been widely utilized for the diagnosis and treatment of prostate cancer; though it is not an ideal tumor marker. Its extensive usage in screening programs has resulted in a large number of unwanted biopsies, over-diagnosis and over-treatment of indolent cancers as well. Hence, various PSA derivatives and PSA-based tests have evolved to improve the accuracy of prostate cancer diagnosis. This article provides an overview of PSA and PSA-based biomarkers and their current role in the screening and diagnosis of prostate cancer.